Effect of oral administration of green tea extract in various dosage schemes on oxidative stress status of mice in vivo - Bártíková Hana; Skálová Lenka; Valentová Kateřina; Matoušková Petra; Szotáková Barbora; Martin Jan; Kvita Vojtěch; Boušová Iva (Acta Pharmaceutica)
Green tea is a favorite beverage and its extracts are popular components of dietary supplements. The aim of the present in vivo study was to obtain detailed information about the effect of a standard green tea extract (Polyphenon, P), at different doses, on antioxidant enzymes and oxidative stress markers in murine blood, liver, small and large intestine. In all doses, P improved the oxidative stress status via an increased content of plasmatic SH-groups (by 21-67 %). Regarding antioxidant enzymes in tissues, the low dose of P had the best positive effect as it elevated the activity of NADPH quinone reductase in liver and small intestine, thioredoxin reductase in small intestine and hepatic superoxide dismutase. Based on these facts, consumption of green tea seems to be safe and beneficial, while consumption of dietary supplements containing high doses of catechins may disturb oxidative balance by lowering the activity of thioredoxin reductase, glutathione S-transferase, glutathione reductase and superoxide dismutase